2023
DOI: 10.1021/acsaem.3c00838
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Mechanism of High Efficiency and Stability of Inverted Polymer Fullerene Solar Cells

Abstract: The performance of organic solar cells has been remarkably improved recently, where the cell structures are important for achieving high efficiency and stability. The formation and accumulation of long-lived charges in the cells are critical for the efficiency and stability of the cells; however, their relations with the cell structures have not yet been clarified from a microscopic viewpoint. Here, we report the microscopic mechanism of high efficiency and stability of inverted polymer fullerene solar cells c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(209 reference statements)
0
2
0
Order By: Relevance
“…For this study, we performed ESR spectroscopy, which has been used successfully to examine organic and perovskite solar cells and related materials, particularly to elucidate the effects of electron transfer and trapping near PEDOT:PSS/CH 3 NH 3 PbI 3 interfaces on device performance. This study takes advantage of the feature that ESR spectroscopy can separate the effect of charge transfer between PEDOT:PSS/CH 3 NH 3 PbI 3 from other factors, for example, including ion migration and the number of defect states of perovskite layers.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we performed ESR spectroscopy, which has been used successfully to examine organic and perovskite solar cells and related materials, particularly to elucidate the effects of electron transfer and trapping near PEDOT:PSS/CH 3 NH 3 PbI 3 interfaces on device performance. This study takes advantage of the feature that ESR spectroscopy can separate the effect of charge transfer between PEDOT:PSS/CH 3 NH 3 PbI 3 from other factors, for example, including ion migration and the number of defect states of perovskite layers.…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we investigate the effects of Sn powder addition to the perovskite precursor solution on band bending at poly­(3,4-ethylenedioxythiophene):poly­(styrenesulfonate) (PEDOT:PSS) HTL/perovskite interfaces in FA 1– x MA x Sn­(I 1– y Br y ) 3 PSCs, using electron spin resonance (ESR) spectroscopy, which has successfully applied for perovskite solar cells and materials and for organic thin film solar cells. In studies on PSCs, ESR spectroscopy has been used to nondestructively and easily characterize the formation of space-charge regions and band bending at buried interfaces in stacked film samples and complete devices. ,, ESR measurements indicated that FA 0.75 MA 0.25 Sn­(I 0.75 Br 0.25 ) 3 shows significant downward band bending near PEDOT:PSS, leading to reduced hole selectivity and enhanced surface recombination. On the other hand, FA 0.75 MA 0.25 Sn­(I 0.75 Br 0.25 ) 3 with Sn powder was found to exhibit upward band bending near PEDOT:PSS owing to reduced Sn 4+ concentration.…”
mentioning
confidence: 99%